S19 The role of lymph node-resident neutrophils in adaptive immunity. (15th November 2017) - Lok, LSC; Stewart, B; Chilvers, ER; Clatworthy, MR
Abstract : Introduction: Neutrophils play a key role in the early response to a diverse range of infectious and inflammatory stimuli. However, persistent neutrophilic inflammation can result in collateral tissue damage, as evident in a number of chronic respiratory diseases. In addition to their role in innate immunity, neutrophils can also shape the adaptive immune response, in part through antigen presentation. Whilst there is accumulating evidence that neutrophils can migrate to draining lymph nodes following infectious challenges, the role of tissue-resident neutrophils in physiological settings is less clear. We hypothesise that neutrophils are present within lymph nodes and can influence adaptive immunity under physiological conditions. Methods: Lymph nodes from unchallenged C57BL/6 and LysM-GFP mice were harvested; single cell suspensions were generated for flow cytometric analysis, and frozen sections stained for confocal microscopy. Two-photon intravital imaging of popliteal lymph nodes was performed to examine neutrophil dynamic behaviour in vivo . Human lymph nodes were harvested from organ donors and analysed by flow cytometry and mass cytometry. Results: Neutrophils were present in lymph nodes in mice without prior inflammatory or infectious challenge. Whilst some neutrophils were within blood vessels (11% in inguinal lymph node, 10% in popliteal lymph node, 12% in mesenteric lymph node) or lymphatic vessels (15% in inguinal lymph node, 21% in popliteal lymph node, 18% in mesenteric lymph node), the majority were located in lymph node tissues. Lymph node neutrophils showed higher surface expression of major histocompatibility complex II (MHCII) compared to blood, bone marrow and splenic neutrophils (figure 1 A). In vivo, neutrophils were capable of immune complex uptake, and their dynamic behaviour differed according to their location within the lymph node. Neutrophils were also present in human lymph nodes, and expressed surface MHCII (figure 1 B). Immune cell profiles of matched lymph nodes and spleen were compared using mass cytometry. Isolated human blood neutrophils upregulated surface MHCII upon ex vivo immune complex stimulation. Conclusion: We have demonstrated the presence of tissue-resident neutrophils within murine and human lymph nodes, and their capacity to express MHCII, potentially influencing the adaptive immune response via antigen presentation.